Використання корпусів текстів у процесі укладання словників - Коцюк, Л. (Лексикографічний бюлетень, 2006)
The article represents the difference that a corpus, and corresponding advances in
lexicology and lexicography can make to form new generation of corpus-based dictionaries. The author raises the question of what the word is and how corpus study can influence the
representation of all its features in the dictionary.